"Jakaru!": comensalidade e socialidade Guarani-Kaiowá - Zotti, Gabriela Barbosa Lima e Santos (Universidade Federal de São Carlos, 2022)
Much has been said about the fabrication of bodies and the construction of the person in the Amerindian world, focusing part of the theoretical and methodological efforts on the shamanic practices of the extraordinary and the ethnographic contexts of the Amazon. This study intends to approach other modes of body agency and construction of the person among the Guarani-Kaiowá, from the southern cone region of the State of Mato Grosso do Sul, more precisely in the Pirakuá Indigenous Land, in the municipality of Bela Vista, on the border with Paraguay. . I focus attention on the everyday ways of making people or, as I defend, on transforming a human into a relative, through commensality and affec- tion, having as a hypothesis the idea that the body of the Ava-Kaiowá Person is not closed in on itself, but open to external affections that, driven by its assemblage, it is possible to absorb becomings-others for its benefit, even if, in extreme contact with these becomings, one runs the risk of ceasing to be related to one's own kin. However, it is positive actions to maintain parenthood, commensality and affection that neutralize these becomings.
"Jakaru!": Guarani-Kaiowá commensality and sociality
Keywords: Comensalidade; Socialidade; Parentalidade; Afeto; Avá-Kaiowá; Commensality; Sociality; Parenthood; Affection; Ava-Kaiowá; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA